IMPLEMENTASI TUGAS DAN WEWENANG KANTOR PERTAHANAN DALAM SENGKETA TANAH DI KOTA KENDARI DITINJAU DARI PERATURAN MENTERI AGRARIA DAN TATA RUANG / BADAN PERTANAHAN NASIONAL NOMOR 11 TAHUN 2016 - Arif, Heru Wira Astaman; Sumanto, Listyowati (Ensiklopedia Education Review, 2024)
Abstract: As the need for land increases, disputes often arise between individuals, legal entities and individuals, government agencies and individuals whose object is land. The problem is what is the role of the Ministry of Agrarian Affairs and Spatial Planning / National Land Agency in its duties and authority as a mediator between parties in land disputes and how to resolve disputes based on Law Number 30 of 2014 concerning Government Administration. This research uses a normative legal research type and is descriptive in nature. Secondary data was analyzed qualitatively. Drawing conclusions using deductive logic. The research results show that the role of the Kendari City Land Office in its duties and authority as a land dispute mediator is obliged to help parties who wish to resolve defense cases non-litigationally and in litigation so that they can be resolved amicably. The authority of the mediator of the Kendari City Land Office, Southeast Sulawesi Province is limited to providing advice or finding the best solution to the parties in dispute, and it is the parties in dispute who have the authority to make decisions in accordance with the provisions of the Regulation of the Head of the National Land Agency Number 3 of 2011 concerning Management, Study and Handling of Cases. Land jo. Regulation of the Minister of Agrarian Affairs/Head of the National Land Agency No. 11 of 2016 concerning Settlement of Land Cases.Keywords: Duties, Authority, Law, Dispute Resolution, Mediator.